The Significance of Country-specific and Common Risk Factors for CEE Government Bond Spreads Changes - Juodžiukynienė, Greta (Ekonomika, 2016)
This paper provides an empirical assessment of the relationship between common European Union and country-specific risk factors of sovereign bond spreads for Central and Eastern European countries over the period of 2004-2014. The model, estimated using Pooled Mean Group techniques, that accounts for both common long-run determinants and cross-country heterogeneities in sovereign bond spreads, tends to suggest that country-specific and common factors are important in the long-run, but common European Union factors are the main determinants of bond spreads in the short-run, i.e., market volatility index series converges with changes of sovereign bond spreads and turns out to be the predominant factor in the short-run. Furthermore, countries with stronger fundamentals have a tendency for lower responsiveness to changes in global risk aversion. The decomposition of changes in spreads for the purpose to compare actual and estimated spreads specifies that during risk-on periods (when the increase of misalignment falls down) there is consistency for increasing of creditworthiness undervaluation.